2021
DOI: 10.18203/2394-6040.ijcmph20213768
|View full text |Cite
|
Sign up to set email alerts
|

Use of routine health information for decision making among health care workers in Marsabit county, Kenya

Abstract: Background: In Kenya today, public health facilities at different levels collect a large amount of routine health (RH) data. However, with the introduction of district health information software (DHIS2), recent evidence has shown low levels of data are used by the targeted stockholders in Kenya. The therefore study aims to examine the association of human resource and information technology factors associated with the frequent use of RH data in decision-making among health-workers in Marsabit county.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…These results indicate that most public health facilities in Kenya lack dependable internet connectivity to support digital health information management for essential medicine supply chains. This corroborates the observations of Aila and Kithuka (2021), who suggest that unreliable internet connections hinder the production, transmission, and efficient utilization of health information for planning and service delivery. Kuyo et al ( 2020) also identified challenges in Uasin Gishu County hospitals related to the use of information from DHIS2, citing factors such as unreliable internet connectivity (47.1%), inadequate user skills (48.6%), non-connected computers (36.7%), and insufficient management support (34.3%).…”
Section: Descriptive Statisticssupporting
confidence: 89%
See 2 more Smart Citations
“…These results indicate that most public health facilities in Kenya lack dependable internet connectivity to support digital health information management for essential medicine supply chains. This corroborates the observations of Aila and Kithuka (2021), who suggest that unreliable internet connections hinder the production, transmission, and efficient utilization of health information for planning and service delivery. Kuyo et al ( 2020) also identified challenges in Uasin Gishu County hospitals related to the use of information from DHIS2, citing factors such as unreliable internet connectivity (47.1%), inadequate user skills (48.6%), non-connected computers (36.7%), and insufficient management support (34.3%).…”
Section: Descriptive Statisticssupporting
confidence: 89%
“…Suhlrie et al ( 2018) cite examples from Malawi where public health facilities are often connected to off-grid electricity systems compared to facilities managed by other entities. Aila and Kithuka (2021) and Muinga et al (2020) note that inconsistent electricity supply challenges hinder the effective use of computers, data analysis, and health information critical for planning and service delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that receiving training HMIS (data collection and reporting), data analysis and data presentation equips health workers with adequate skills and expertise on how to utilize routine health information while making decisions. The findings also agree with Aila (2021) who argued that training that improves health workers skills in data gathering, analysis, interpretation, and information management increases their likelihoods of utilizing routine health data in making decisions.…”
Section: Ethical Approvalsupporting
confidence: 88%